2017
DOI: 10.1093/schbul/sbx073
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Brain Activation During Theory of Mind Tasks in Schizophrenia: A Meta-Analysis

Abstract: Social cognition abilities are severely impaired in schizophrenia (SZ). The current meta-analysis used foci of 21 individual studies on functional abnormalities in the schizophrenic brain in order to identify regions that reveal convergent under- or over-activation during theory of mind (TOM) tasks. Studies were included in the analyses when contrasting tasks that require the processing of mental states with tasks which did not. Only studies that investigated patients with an ICD or DSM diagnosis were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 108 publications
3
68
0
3
Order By: Relevance
“…Additional analysis of which part of the covariance were important for classification, revealed that the only feature surviving correction for multiple comparisons was the variance within the left TPJ. This region has been associated with social cognition and ToM in several previous studies (Bodnar et al, 2014;Dodell-Feder, Tully, Lincoln, & Hooker, 2014;Kronbichler, Tschernegg, Martin, Schurz, & Kronbichler, 2017) and was also a prominent region in the decomposition methods to presented below. For more details on this analysis wee the "interpretation of covariance features for HSA classification" section in Data S1.…”
Section: Classification Of Social Anhedoniamentioning
confidence: 86%
“…Additional analysis of which part of the covariance were important for classification, revealed that the only feature surviving correction for multiple comparisons was the variance within the left TPJ. This region has been associated with social cognition and ToM in several previous studies (Bodnar et al, 2014;Dodell-Feder, Tully, Lincoln, & Hooker, 2014;Kronbichler, Tschernegg, Martin, Schurz, & Kronbichler, 2017) and was also a prominent region in the decomposition methods to presented below. For more details on this analysis wee the "interpretation of covariance features for HSA classification" section in Data S1.…”
Section: Classification Of Social Anhedoniamentioning
confidence: 86%
“…Similarly, aberrant neural activation has been observed during mentalizing. Schizophrenia patients showed hypoactivation in several areas related to mentalizing, including medial prefrontal cortex, posterior temporoparietal junction and ventromedial prefrontal cortex, as well as hyperactivation in the dorsal section of temporoparietal junction.…”
Section: Functional Neuroimaging and Cognitive Impairment In Schizophmentioning
confidence: 87%
“…29,30 The second main hypothesis was that, according to the Shared Vulnerability Model, 10 the initial differences between HC and patients with schizophrenia in creative performance would be, at least partially, due to the impairment in EF observed in schizophrenia. Given the previous evidence of the relation between ToM and creativity among healthy people, [33][34][35] along with the underlying shared brain structures 36,37,39 and the impairment shown in ToM in schizophrenia, 30,31 we decided to analyze whether ToM played a mediatory role in the relation between schizophrenia and creativity. This hypothesis was also confirmed.…”
Section: Discussionmentioning
confidence: 99%